A colorimetric method for use within portable test kits for nitrate determination in various water matrices. Issue 4 (16th January 2017) - Murray, Eoin; Nesterenko, Ekaterina P.; McCaul, Margaret; Morrin, Aoife; Diamond, Dermot; Moore, Breda
Abstract : A method using zinc powder in conjunction with the common Griess assay was developed for the detection of nitrate in water. Abstract : A method using zinc powder in conjunction with the common Griess assay was developed for the detection of nitrate in water. This method is applicable to portable water test kits and allows for the accurate determination of nitrate in freshwater. The linear range for the method was shown to be 0.5–45 mg L −1 NO3 − and the limit of detection (LOD) was 0.5 mg L −1 NO3 − . The proposed method was validated over a five-day period and acceptable recovery and uncertainties were achieved when analysing freshwater matrices. The performance of the developed method was compared to an ISO-accredited ion chromatographic (IC) method by carrying out blind sample analysis. A good agreement between the two methods was achieved as comparable concentrations were determined using each method. In addition, the Zn method was compared to the performance of a novel solid-phase reagent method, previously developed within the group. The most accurate performance was demonstrated by the Zn powder method when analysing freshwater samples. The novel solid-phase reagent method demonstrated the greater accuracy when analysing seawater samples.